Inovasi Pengembangan Potensi Sumber Daya Desa Andalan pada Sektor Pariwisata dan Ekonomi Kreatif di Masa Pandemi Covid-19 - Kuswaji Dwi Priyono; Syaifudin, Muhammad Arif (Universitas Muhammadiyah Surakarta, 2022)
The purpose of this service is to analyze and develop the potential of community resources in handling and managing tourism potential and the creative economy in Andalan Village. The method used is descriptive qualitative with primary data collection techniques in the form of interviews, observations and documentation. As a result, Andalan Village has great potential in tourism and the creative economy. Andalan village has the potential for agro-tourism, religious tourism, cultural tourism, mainstay coffee, ares chips and cashew jam. After the seminar was held which was attended by all village officials and creative economy business actors, it is hoped that the community will understand better in managing every potential that exists in this village at the tip of the island of Lombok, namely Andalan